Inequality within countries is falling: Underreporting robust estimates of world poverty, inequality, and the global distribution of income - Maxim Pinkovskiy; Xavier Sala-i-Martin; Kasey Chatterji-Len; William Nober (Federal Reserve Bank of New York, 2024)
Household surveys suffer from persistent and growing underreporting. We propose a novel procedure to adjust reported survey incomes for underreporting by estimating a model of misreporting whose main parameter of interest is the elasticity of regional national accounts income to regional survey income, which is closely related to the elasticity of underreporting with respect to income. We find this elasticity to be substantial but roughly constant over time, implying a large but relatively constant correction to survey-derived inequality estimates. Underreporting of income by the bottom 50 percent of the world income distribution has become particularly important in recent decades. We reconfirm the findings of the literature that global poverty and inequality have declined dramatically between 1980 and 2019. Finally, we find that within-country inequality is falling on average and has been largely constant since the 1990s.
Keywords: C83; D31; D33; 330; poverty; inequality; welfare; survey underreporting